Current challenges and prospects of quail farming in Malaysia: A review - Zhi Y. Wong; Anatasha A. Napolean; Norfarah A. Zamani; Chu L. J. Frederick; Rohaida A. Rasid; Su C. L. Candyrine; Mohammad M. Rahman; Mohamad A. Kalam; Tyagita Hartady; Md S. A. Bhuiyan (German Multidisciplinary Publishing Center (GMPC), 2025)
Quail farming in Malaysia offers significant potential for agricultural diversification and economic growth. This report examines the current challenges and prospects of this emerging industry. Key challenges include inadequate disease control measures, high feed costs, limited availability of quality breeding material, and insufficient farmer knowledge of modern breeding techniques. Additionally, environmental concerns and regulatory requirements hinder the industry's expansion. Despite these obstacles, the prospects for quail farming in Malaysia are good. The growing demand for quail products, driven by their nutritional value and increasing popularity among health-conscious consumers, offers significant market opportunities. Innovation in breeding, improved disease management, and supportive government policies are critical to overcoming these challenges. The report emphasizes the importance of utilizing sustainable breeding methods, optimizing feed utilization, and enhancing genetic resistance to diseases in quails. Collaborative efforts among researchers, policymakers, and farmers are crucial to unlocking the full potential of quail farming in Malaysia and ensuring its long-term sustainability and profitability.